The role of D4 receptor gene exon III polymorphisms in shaping human altruism and prosocial behavior - Jiang, Yushi; Chew, Soo Hong; Ebstein, Richard P. (Frontiers in Human Neuroscience, 2013)
Human beings are an extraordinarily altruistic species often willing to help strangers at a considerable cost (sometimes life itself) to themselves. But as Darwin noted “…he who was ready to sacrifice his life, as many a savage has been, rather than betray his comrades, would often leave no offspring to inherit his noble nature”. Hence, this is the paradox of altruism. Twin studies have shown that altruism and other prosocial behavior show considerable heritability and more recently a number of candidate genes have been identified with this phenotype. Among these first provisional findings are genes encoding elements of dopaminergic transmission. In this article we will review the evidence for the involvement of one of these, the dopamine D4 receptor (DRD4) gene, in shaping human prosocial behavior and consider the methodologies employed in measuring this trait, specific molecular genetic findings and finally, evidence from several Gene x Environment (GxE) studies that imply differential susceptibility of this gene to environmental influences.